A case report on methotrexate induced pancytopenia - Devulapallli, Meghana; Durga Prasad, T. S.; Narasimha Kumar, G. V.; Avanthi, B.; Shabana Banu, S. K. (International Journal of Basic & Clinical Pharmacology, 2017)
Systemic lupus erythematosus (SLE) is a non-specific systemic inflammatory disease that affects various organ systems in the body leading to a wide spectrum of clinical presentations. The management of SLE includes therapy with immunosuppressant agents who have a narrow safety range and a wide adverse effect profile. Methotrexate discussed in this case report is one of such drugs whose short term and long term usage has been associated with various adverse events that affect the individuals quality of life. So, it is always advisable to take prophylactic measures and to provide patient education to detect and prevent adverse events at the earliest.